2016
DOI: 10.1152/ajprenal.00513.2015
|View full text |Cite
|
Sign up to set email alerts
|

Resistant starch alters gut microbiome and metabolomic profiles concurrent with amelioration of chronic kidney disease in rats

Abstract: Patients and animals with chronic kidney disease (CKD) exhibit profound alterations in the gut environment including shifts in microbial composition, increased fecal pH, and increased blood levels of gut microbe-derived metabolites (xenometabolites). The fermentable dietary fiber high amylose maize-resistant starch type 2 (HAMRS2) has been shown to alter the gut milieu and in CKD rat models leads to markedly improved kidney function. The aim of the present study was to identify specific cecal bacteria and ceca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
170
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(193 citation statements)
references
References 84 publications
14
170
3
Order By: Relevance
“…Our group recently reported that the prebiotic amylose maize resistant starch, which reaches the colon undigested and is metabolized by bacteria to short-chain fatty acids, improved creatinine clearance and reduced kidney fibrosis in CKD rats [60]. A follow-up study revealed marked improvements in serum, urine and cecal fluid metabolomics in conjunction with decreased gut microbial dysbiosis [61]. A meta-analysis of controlled feeding trials found that fibre supplementation significantly decreased serum urea levels in a pooled cohort of 143 participants but there was significant interstudy heterogeneity and urea lowering was not a doseresponse effect [62].…”
Section: Urea Toxicitymentioning
confidence: 99%
“…Our group recently reported that the prebiotic amylose maize resistant starch, which reaches the colon undigested and is metabolized by bacteria to short-chain fatty acids, improved creatinine clearance and reduced kidney fibrosis in CKD rats [60]. A follow-up study revealed marked improvements in serum, urine and cecal fluid metabolomics in conjunction with decreased gut microbial dysbiosis [61]. A meta-analysis of controlled feeding trials found that fibre supplementation significantly decreased serum urea levels in a pooled cohort of 143 participants but there was significant interstudy heterogeneity and urea lowering was not a doseresponse effect [62].…”
Section: Urea Toxicitymentioning
confidence: 99%
“…Our group previously reported that feeding uremic rats amylose maize-resistant starch (a prebiotic) improved creatinine clearance and reduced kidney inflammation and fibrosis [123]. A follow-up study revealed marked improvements in serum, urine, and intestinal fluid metabolomics in conjunction with decreased gut microbial dysbiosis [124]. Resistant starches transit to the colon undigested and are metabolized by bacteria to short-chain fatty acids which are important nutrients to enterocytes.…”
Section: Interventions To Attenuate Gut Microbiome Disturbances In Ckdmentioning
confidence: 99%
“…Results from animal studies show favorable effects of a high fiber diet in restoring intestinal microbiome, and plasma, cecal, and urine metabolome (124). Similarly, rats with CKD fed high resistant starch diet had retardation in progression of CKD.…”
Section: Modulation Of Gut Microbiotamentioning
confidence: 99%